2021
DOI: 10.1037/cdp0000357
|View full text |Cite
|
Sign up to set email alerts
|

Community providers’ experiences with evidence-based practices: The role of therapist race/ethnicity.

Abstract: Objectives: Examining therapists' experiences implementing evidence-based practices (EBPs) is fundamental to understanding how these interventions are perceived, adapted, and delivered in community settings. However, little is known about racial/ethnic variation in the experiences of therapists serving racial/ethnic minority youth and their families. Through an innovative QUAN ¡ qual ¡ QUAN mixed-methods approach, we examined differences in therapists' perceptions, adaptations performed, and client-engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Qualitative analyses of Modifying Presentation descriptions revealed therapists tailoring active teaching techniques in creative ways; modifying language for developmental and cultural needs; and personalizing EBP content to clients’ lived experiences. Such adaptations are consistent with therapists using their local knowledge and multicultural competence to tailor EBP presentation for their clients (Ramos et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Qualitative analyses of Modifying Presentation descriptions revealed therapists tailoring active teaching techniques in creative ways; modifying language for developmental and cultural needs; and personalizing EBP content to clients’ lived experiences. Such adaptations are consistent with therapists using their local knowledge and multicultural competence to tailor EBP presentation for their clients (Ramos et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Agencies involved in the PEI initiative shared that having bilingual therapists was one of their engagement strategies (Regan et al, 2017 ). Researchers have found that Latino/a therapists involved in PEI made more culturally congruent adaptations to EBPs than White therapists (Ramos et al, 2020 ). Latino/a therapists frequently made language-based adaptations to the interventions to improve fit with clients.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is also aligned with recent guidelines for the provision of culturally robust PCIT for marginalized groups (McCabe et al, 2020). Importantly, these types of data-driven adaptations have been shown to lead to fewer client engagement issues among Latinx families receiving care in community settings (Ramos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%